The McElroy Brothers, New Media, and the Queering of White Nerd Masculinity. Issue 2 (June 2019) - Fine, Leigh E.
Nerd masculinity is in the midst of a cultural rebirth. Podcasters the McElroy Brothers—Justin, Travis, and Griffin—are exemplars of how nerds queer contemporary masculinity discourse. Their podcasts' multidimensional characters, bodily practices, and inclusive language reconstruct a nerd masculinity that does not pine for hegemonic masculinity as nerd media of the past. However, while the Brothers' performance of masculinity may illuminate new frontiers for the inclusion of gender and sexual diversity, it yet retains an inextricable connection to their Whiteness. Thematic analysis of 41 episodes across three of the McElroy's properties shows how the Brothers reconceptualize nerd masculinity while highlighting their lack of transformative attention to matters of race.